The Development of a Highly Sensitive Liquid Chromatography–Tandem Mass Spectrometry (LC-MS/MS) Method for the Validation of Flualprazolam and Isotonitazene in Serum - Murat Akbaba; Aysun Baransel Isir (Applied Sciences, 2025)
Objectives: This study aimed to develop and validate a sensitive and reliable liquid chromatography–tandem mass spectrometry (LC-MS/MS) method for the quantification of flualprazolam and isotonitazene in serum samples to address critical gaps in forensic and clinical toxicology. Materials and Methods: A single-center validation study was conducted using serum samples spiked with analyte standards. Analytical parameters, including linearity, precision, recovery, the limit of detection (LOD), and the limit of quantification (LOQ), were evaluated in accordance with international guidelines. The LC-MS/MS method employed a Shimadzu Triple Quadrupole™ MS 8045 system with solid-phase extraction (SPE) for sample preparation. Results: The method exhibited high linearity for flualprazolam (r2 = 0.997) and isotonitazene (r2 = 0.999) over a concentration range of 1–100 ng/mL. The LODs were determined as 0.608 ng/mL and 0.192 ng/mL, and the LOQs were 1.842 ng/mL and 0.584 ng/mL for flualprazolam and isotonitazene, respectively. Recovery tests yielded results within the acceptable range of 70–120%. Flualprazolam demonstrated recovery rates of 98.0% and 97.0% at theoretical concentrations of 10 ng/mL and 50 ng/mL, respectively. In contrast, the isotonitazene recovery rates were slightly lower, measuring 75.5% at 10 ng/mL and 71.9% at 50 ng/mL, suggesting minor matrix effects that could influence its quantification. Precision analysis, including both repeatability and reproducibility, highlighted the reliability of the method. The %RSD values for flualprazolam were consistently below 7.07%, with mean concentrations closely aligning with theoretical values across fortification levels. For isotonitazene, the %RSD values remained below 6.24%, although recoveries at higher concentrations indicated potential challenges in matrix interaction. Conclusions: This validated LC-MS/MS method offers high sensitivity, precision, and recovery for detecting flualprazolam and isotonitazene in serum, filling a critical need in toxicological investigations. Further validation in other biological matrices is recommended to broaden its applicability.